2018
DOI: 10.3390/v10090468
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Infection Dynamics of Cafeteria Roenbergensis Virus

Abstract: The discovery of giant viruses in unicellular eukaryotic hosts has raised new questions on the nature of viral life. Although many steps in the infection cycle of giant viruses have been identified, the quantitative life history traits associated with giant virus infection remain unknown or poorly constrained. In this study, we provide the first estimates of quantitative infection traits of a giant virus by tracking the infection dynamics of the bacterivorous protist Cafeteria roenbergensis and its lytic virus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Although CroV encodes some translation components, it lacks ribosomal proteins and therefore depends on host translation. Newly synthesized CroV particles are released as early as 5-6 hours post infection (hpi), while the majority of extracellular virions appear during host cell lysis at 15-22 hpi (Taylor et al , 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Although CroV encodes some translation components, it lacks ribosomal proteins and therefore depends on host translation. Newly synthesized CroV particles are released as early as 5-6 hours post infection (hpi), while the majority of extracellular virions appear during host cell lysis at 15-22 hpi (Taylor et al , 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Future work at higher MOPs or with different chloroviruses may need to incorporate MOP-dependencies (cf. Brown & Bidle, 2014; Taylor et al ., 2018). Finally, our methods estimated an average burst size, while studies in other viruses have shown that per-cell burst size can vary by orders of magnitude (Kannoly et al ., n.d.; Delbrück, 1945; Timm & Yin, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…By leveraging the distinction between MOP and MOI, the mOSG and mP assays measure more traits than assays based on one or the other (e.g. Van Etten et al ., 1983; Tomaru et al ., 2005; Taylor et al ., 2018). The high-throughput flow cytometry also makes them more efficient than e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of C. burkhardae , the giant virus CroV and the virophage mavirus, the numbers of viral progeny depend on the mode of infection among other factors. CroV-mavirus coinfection (CroV is inhibited by mavirus) and reactivation (both CroV and mavirus replicate, ~130-CroV particles, ~1000 mavirus particles) of the integrated mavirus virophage lead to the replication and release of infectious mavirus particles [ 17 , 18 ]. Coinfection of host cells with CroV and mavirus leads to the inhibition of CroV replication, as mavirus uses the molecular infrastructure of the cytoplasmic CroV factory for its own replication [ 5 , 16 ].…”
Section: Introductionmentioning
confidence: 99%